Faktor Penentu Penghasilan Kafe di Perkotaan - Fathur, Muhammad Fathurullah Syahrul; Abdul Rahman Razak; Mirzalina Zaenal (Departemen Ilmu Ekonomi, UNHAS, 2024)
This study aims to understand and analyze how big the influence of capital, the total of labour and length of business to the income of cafe business in Makassar City. That data analysis method that used are multiple linear regression with spss 25 application. The data that used by this study are primary data that collected by questionnaire and interview to cafe business owner in Makassar city. Based on the estimation result shows that capital, labour and length of business variable has positive influence and significant to income. This study shows the more capital, total labour and length of business means the higher the income that will be received by the cafe business owner in Makassar city.